International standardization of clinical stabilometry (Minutes of the meeting of posturologists, Paris 07.10.2015) - Gagey, Pierre-Marie (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Stabilometry, like any technology, generates its own language that must be enslaved to the requirement of the psychology of scientific discovery: the communication between minds. We know of no other way of this enslavement than normalization. Normalization that has proved impossible apart from its specification by a research prospect, for example, trying to treat functional disorders of the upright postural control system. This research, which, oddly enough, for the time being, only Latin therapists are interested in.